A lei 11.645/08: história, movimentos sociais e mudança curricular - Fanelli, Giovana de Cássia Ramos (2018)
The present work sought to understand historically how the process of formation of Law 11.645 / 08, which includes in the official curriculum of the public and private education network, the obligatoriness of the theme "History and Afro-Brazilian and Indigenous Culture" in the subjects of History , Arts and Portuguese Language. Prior to this law, in 2003, Law 10,639 was approved, which incorporated Afro-Brazilian History and Culture into the school curriculum, resulting from a long process of Black Claims in Brazil. Law 11.645 / 08 establishes in the context of the Indigenous Claims in Brazil, the historical achievements of the 1988 Constitution, the educational changes promoted by the Law of Guidelines and Bases of Brazilian National Education (Law 9394/96), the claims by a not colonizing and intercultural school by Brazilian indigenous teachers, and, finally, includes in the affirmative policies of Lula government (2003-2010). It was sought to discuss the Brazilian Indigenous Claims and its main demands, the contributions of historians and anthropologists in deconstruction of the "generic indian" and the actions of MEC related to the indigenous theme in the school. The research started from two hypotheses: the first is that Law 11.645 / 08 was the result of the claim of the Brazilian Indigenous Movement, especially the indigenous teachers; the second is that the institutional environment of Lula government, with emphasis on affirmative public policies, favored the approval of the norm. The methodological procedures in the analysis of all the official documentation that refers to the bill, the identification of the subjects involved through the written sources, as well as the audiences of the debates in the committees of the Federal House and Senate, had as theoretical reference Goodson (2001, 2008), Thompson (1987), Faria Filho (1998) and Ginzburg (2002)